Inhalation Exposure to PCB from Contaminated Indoor Air—How Much Is Absorbed into the Blood? - Martin Kraft; Knut Rauchfuss; Hermann Fromme; Lothar Grün; Silvia Sievering; Barbara Köllner; Yvonni Chovolou (Pollutants, 2021)
Polychlorinated biphenyls (PCBs) were used in many construction products until their banning in the 1970s and 1980s. Nonetheless, exposure to PCBs from contaminated indoor air is still an important public health issue. The aim of our study was to estimate the contribution of PCB congeners in indoor air to the levels of PCBs in human blood. We analyzed all 209 PCB congeners in the blood of 35 individuals exposed to PCBs from contaminated indoor air. For each individual, we measured the six marker indicators PCB28, PCB52, PCB101, PCB138, PCB153 and PCB180 in indoor air at the workplace. Statistically significant correlations between PCB-contaminated indoor air and the existence of the sum of mono-, di-, tri-, tetra- and pentachlorinated biphenyls (∑PCB1–127) in the blood of the exposed individuals were found. We quantified the proportions of PCBs that are absorbed into the blood via inhalation of contaminated indoor air. Inhalation of PCBs from contaminated indoor air, especially in children, adolescents and younger adults, may lead to PCB blood burdens that are higher than general PCB background levels or in approximately the same range.